Native parasitoids associated with fruit flies (Diptera: Tephritidae) in cultivated and wild fruit crops in Casamance (Senegal) - Vayssières, Jean-François; Adandonon, A.; N'Diaye, O.; Sinzogan, A.A.C.; Kooymann, C.; Badji, K.; Rey, J.; Wharton, R. (Entomological Society of Southern Africa, 2012)
Fruit flies are pests of economic importance inWest Africa due to their quarantine status and losses recorded in fruits and vegetables. Before the introduction of exotic species of parasitoids against any exotic fruit fly species, it is fundamental to first determine the presence and monitor the native parasitoid species.This work was carried out in Casamance (Senegal), during the rainy season of 2010, with sampling of 5191 fruits from 22 plant species. Seven species of parasitoids (all Braconidae) were recorded and reared from six fruit species. The parasitoids included Fopius caudatus (Szépligeti), F. silvestrii (Wharton), F. desideratus (Bridwell), Diachasmimorpha fullawayi (Silvestri), D. carinata (Szépligeti), Psyttalia cosyrae (Wilkinson) and P. concolor (Szépligeti). The most abundant species was F. caudatus (63.97 %). The overall mean parasitism rate observed in all samples was 2.4 ± 1.3 %. Ceratitis cosyra (Walker) (77 %) was the host fly most commonly reared from fruits yielding parasitoids including F. caudatus. Annona senegalensis Pers. was the fruit species most frequently infested by fruit flies and Saba comorensis (Boj. ex DC) Pichon fruits had the highest parasitism rates. In the current work, there were no parasitoids reared from the recently introduced pest, Bactrocera invadens Drew, Tsuruta and White. This is the first report of all these reared parasitoids, except D. fullawayi, in Senegal.